HUBUNGAN PENGETAHUAN DAN MOTIVASI PERAWAT TENTANG TERAPI INTRAVENA DENGAN PENCEGAHAN PLEBITIS DI RUANG RAWAT INAP RSUD RADEN MATTAHER KOTA JAMBI - Ayu Rahayu; Hasyim Kadri (Universitas Baiturrahim, 2017)
Background : Plebitis is one nosocomial infection due to complications experienced by patients installation of intravenous therapy in the hospital. Based on the initial survey discovered that the average incidence in the Room plebitis Inpatient Hospital Raden Mattaher Jambi, of 40 patients a day was found as much as 7-8 patients experienced plebitis. The skills of nurses in intravenous therapy action influenced the knowledge and motivation to take preventive plebitis. Method : This research is a quantitative research using cross sectional study design that aims to determine the relationship of knowledge and motivation of nurses on intravenous therapy with plebitis prevention. Methods of data collection is done by filling out the questionnaire and data analysis methods using univariate and bivariate che-square test. The result showed 50 respondents as many as 75% of respondents who have a high knowledge plebitis prevention, while 25% had high knowledge did plebitis prevention and as much as 80.7% of respondents have high motivation to prevent plebitis, while as many as 19.3% of respondents did not prevention plebitis. There is a significant relationship (p-value = 0.002> 0.005) between knowledge and (p-value = 0.000> 0.005) on the prevention plebitis motivation. Suggested to hospitals Raden Mattaher Jambi need for a complete infrastructure to support the adoption of intravenous therapy better.